2015
DOI: 10.4103/2008-322x.163770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monocular deprivation on rabbit neural retinal cell densities

Abstract: Purpose:To describe the effect of monocular deprivation on densities of neural retinal cells in rabbits.Methods:Thirty rabbits, comprised of 18 subject and 12 control animals, were included and monocular deprivation was achieved through unilateral lid suturing in all subject animals. The rabbits were observed for three weeks. At the end of each week, 6 experimental and 3 control animals were euthanized, their retinas was harvested and processed for light microscopy. Photomicrographs of the retina were taken an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
0
3
0
2
Order By: Relevance
“…These retinal microvascular changes in AEs could indicate abnormalities or slow development of the macula linked to a lack of normal visual experience. Studies in animal models have shown that monocular deprivation leads to a decrease in retinal ganglion cell density [12][13][14] and an overall thinning of the inner plexiform layer. 15,16 Ocular deprivation is also believed to result in a decrease in the number of synaptic connections in the inner plexiform layer 17 associated with a decrease in retinal ganglion cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…These retinal microvascular changes in AEs could indicate abnormalities or slow development of the macula linked to a lack of normal visual experience. Studies in animal models have shown that monocular deprivation leads to a decrease in retinal ganglion cell density [12][13][14] and an overall thinning of the inner plexiform layer. 15,16 Ocular deprivation is also believed to result in a decrease in the number of synaptic connections in the inner plexiform layer 17 associated with a decrease in retinal ganglion cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Eyelid suture at P15 in the MD rats results in low-contrast vision of the same eye within a time-sensitive window critical for visual development 52 . Such deteriorated vision can lead to long-term synaptic depression along with reduced cell densities in the retina 52 54 . In amblyopia, the loss of vision is thought to be driven by the lack of visual brain development independent of eye abnormalities 52 .…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 In addition, the intraocular pressures of the MD and control eyes were 8.67 ± 0.380 mm Hg and 8.5 ± 0.365 mm Hg, respectively (n = 6 per group; t = 0.316; degrees of freedom = 10; P = 0.758). Other reasons for the drop in ERG amplitudes might be temporary impairment of retinal function, 42 as well as the reduction of ganglion, inner nuclear, and outer nuclear cells 49 ; axial elongation of eye 50 ; and ischemic insult 51 in the deprived eye. We will examine the specific cause of ERG amplitude reduction in future studies.…”
Section: Discussionmentioning
confidence: 99%